COMPARATIVE STUDY ON THE INTENSITY OF Mycobacterium leprae EXPOSURE BETWEEN HOUSEHOLD AND NONHOUSEHOLD CONTACT OF LEPROSY - Arsyad, Yuniarti; Jifanti, Friska; Amiruddin, Muhammad Dali; Anwar, Anis Irawan; Adriaty, Dinar; Wahyuni, Ratna; Iswahyudi, Iswahyudi; Agusni, Indropo (Institute of Topical Disease, 2012)
Leprosy stills a public health problem in West Sulawesi which has a Case Detection Rate (CDR) around 43.69/100.000 population. Household contacts of leprosy are a high risk group to be infected, due to droplet infection mode of transmission of the disease. A nose swab examination and serological study was conducted to detect exposure of M. leprae of people who live in leprosy endemic area. Detection of M. leprae in the nasal cavity will represent the exposure rate from outside and the measurement of specific antibody is represented the result of exposure to the immune system. Two group of inhabitants (30 household contacts of leprosy and 30 nonhousehold contacts) were involved in the study. They live in Banggae district, a leprosy endemic area of Majene Regency, West Sulawesi. Sixty nose swab samples and sixty capillary blood samples from the same invidividuals of the two groups were collected and sent to Leprosy laboratory of the Institute of Tropical Disease, Airlangga University Surabaya. A Polymerase Chain Reaction (PCR) was performed to the nose swab samples for detection of M. leprae. The blood samples were examined serologically to measure the level of anti PGL-1 antibody. PCR examination of nose swab samples showed 1/30 positive result in the household contact group and also 1/30 positive result in non-household contact of leprosy (statistically no significant difference, p > 0.05). Serological study showed higher sero-positive result in the household contact group (15/30 or 50%) compared to non-household contact (11/30 or 36%), but statistical calculation revealed no significant difference between the two groups (p > 0.05) on sero-positive results of leprosy. It is concluded that household and non-household contact in leprosy have the same risk to be affected by the disease. The term of household and non-household contact need to be redefined. The possible role of exposure from the environment was also discussed, especially from non-human resource of M. leprae.